Leveraging genetic variability for MGIDI based identification of chickpea (Cicer arietinum) landraces with improved phosphorus use efficiency - BHARATH, SOMSOLE; KUMAR, NEERAJ; PATIL, B S; MEENA, MAHESH C; DASGUPTA, UTTARAYAN; JOSHI, NILESH; DANAKUMARA, THIPPESWAMY; KUMAR, ASHOK; UMASHANKAR; KUMAR1, SUDHIR; BHARADWAJ, C (The Indian Journal of Agricultural Sciences, 2025)
Known for its high nutritional content, chickpea (Cicer arietinum L.) is grown around the world, but its productivity is constrained by numerous biotic and abiotic factors including low phosphorus (P) stress. As it is grown majorly in marginal lands, the availability of P to the crop is greatly reduced. To overcome the problem, phosphorus use efficiency (PUE) of the chickpea needs to be improved. The first step to any breeding programme is to understand the phenotypic variability and adaptive responses of the plants under stress conditions and to employ the effective approaches to identify the superior genotypes with desirable traits. The present study was carried out during 2024–25 at ICAR-Indian Agricultural Research Institute, New Delhi, utilized hydroponic to analyze the root traits under contrasting P conditions in chickpea. The experiment was laid out in a completely randomized design (CRD) with 5 replications of each genotype. The majority of root associated traits in genotypes tolerant to low P exhibited marked increase in growth and development under low P conditions. The PUE index was used to categorize the genotypes, identifying IG5860, ILC0 (Moldova), and ILC1906 as efficient, and ILC0 (CR), ILC12022, and ILC595 were classified as inefficient. The MGIDI served as a powerful, easy-to-use, and adaptable tool for conducting multitrait analysis on complex multivariate data and MGIDI analysis revealed IG5876, ILC0 (Moldova) and ILC1906 as the best genotypes under low P conditions and ILC0 (Russia), IG5848, and ILC0 (Moldova) under adequate P conditions. These contrasting genotypes represent promising candidates for subsequent field evaluation and, upon confirmation under field conditions, for incorporation into breeding and mapping programme.